Hispanics and violent crime in the United States: examining the effect of segregation - Mecom, Dorothy (2002)
The purpose of this study focuses on Hispanics and violent crime. Previous studies (Krivo and Peterson, 1993, Shihadeh and Flynn, 1996) analyze crime rates among blacks; however, the research on Hispanics is very limited (Massey and Denton, 1992). The majority of sociological studies analyze racial residential segregation in order to explain higher rates of violent crime among blacks. (Peterson and Krivo, 1993; Frey and Farley, 1996.) Most researchers employ the Index of Dissimilarity (D), which measures evenness (distribution of the population), in order to measure segregation. (Fischer and Massey, 2000). In this study, I plan to fill the gap in previous literature by employing the segregation measure of evenness (D), along with several other variables, in order to see if it has a positive effect on Hispanic violent crime, specifically homicide